Effects of UV radiation on transcript and metabolite accumulation are dependent on monochromatic light background in cucumber. Issue 3 (23rd September 2021) - Palma, Carolina Falcato Fialho; Castro‐Alves, Victor; Rosenqvist, Eva; Ottosen, Carl‐Otto; Strid, Åke; Morales, Luis Orlando
Abstract: During recent years, we have advanced our understanding of plant molecular responses to ultraviolet radiation (UV, 280–400 nm); however, how plants respond to UV radiation under different spectral light qualities is poorly understood. In this study, cucumber plants ( Cucumis sativus "Lausanna RZ F1") were grown under monochromatic blue, green, red, and broadband white light in combination with UV radiation. The effects of light quality and UV radiation on acclimatory responses were assessed by measuring transcript accumulation of ELONGATED HYPOCOTYL 5 ( HY5 ), CHALCONE SYNTHASE 2 ( CHS2 ), and LIGHT HARVESTING COMPLEX II ( LHCII ), and the accumulation of flavonoids and hydroxycinnamic acids in the leaves. The growth light backgrounds differentially regulated gene expression and metabolite accumulation. While HY5 and CHS2 transcripts were induced by blue and white light, LHCII was induced by white and red light. Furthermore, UV radiation antagonized the effects of blue, red, green, and white light on transcript accumulation in a gene‐dependent manner. Plants grown under blue light with supplementary UV radiation increased phenylalanine, flavonol disaccharide I and caffeic acid contents compared to those exposed only to blue light. UV radiation also induced the accumulation of flavonol disaccharide I and II, ferulic acid hexose and coumaric acid hexose in plants grown under green light. Our findings provide a further understanding of plant responses to UV radiation in combination with different light spectra and contribute to the design of light recipes for horticultural practices that aim to modify plant metabolism and ultimately improve crop quality.